Transforming Madrasah Education: Public Service Delivery and Digital Integration in Kemenag Sleman - Faisal Falahuddin (Journal of Islamic Education Management Research, 2023)
Purpose – This study aims to explore the implementation of public service delivery by the Madrasah Education Section in Kemenag Sleman, focusing on operational procedures, educator and student development programs, religious moderation, tolerance, and digital transformation initiatives. Design/methods/approach – Adopting a qualitative research design, the study utilized descriptive analysis to understand the intricacies of public service delivery in the context of madrasah education. Key methods included structured face-to-face interviews with the Head of Madrasah Education and an extensive review of relevant documents. This approach enabled a detailed examination of the service offerings and operational dynamics within the Madrasah Education Section. Findings – The study reveals a comprehensive array of services and programs, including operational permits, development of educators and students, and initiatives in religious moderation and digital transformation. It highlights the integration of digital tools in educational management and curriculum development, addressing the dynamic needs of contemporary madrasah education. Research implications/limitations – The findings offer valuable insights into the public service delivery mechanisms within religious educational settings. However, the study's focus on a single district limits its generalizability, suggesting the need for further research in diverse regions for a more comprehensive understanding. Practical implications – This research underscores the importance of adapting educational services to technological advancements and societal changes, emphasizing digital integration in educational management and curriculum development to enhance the quality of education and cater to diverse student needs. Originality/value – The study contributes significantly to the discourse on public service implementation in educational settings, particularly in religious institutions. It provides a unique perspective on how madrasah education can evolve to remain effective and relevant amidst changing societal dynamics and technological advancements.